2012
DOI: 10.1103/physreve.86.021112
|View full text |Cite
|
Sign up to set email alerts
|

Brownian transport in corrugated channels with inertia

Abstract: The transport of suspended Brownian particles dc-driven along corrugated narrow channels is numerically investigated in the regime of finite damping. We show that inertial corrections cannot be neglected as long as the width of the channel bottlenecks is smaller than an appropriate particle diffusion length, which depends on the the channel corrugation and the drive intensity. Being such a diffusion length inversely proportional to the damping constant, transport through sufficiently narrow obstructions turns … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 51 publications
0
22
0
3
Order By: Relevance
“…Important examples include Brownian motors [38,39], active Brownian motion of self-propelled particles [40][41][42][43][44][45][46], hot Brownian motion [47], and Brownian motion in shear flows [48]. Recent theoretical studies also found that the inertias of particles and surrounding fluids can significantly affect the Brownian motion in nonequilibrium systems [49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Important examples include Brownian motors [38,39], active Brownian motion of self-propelled particles [40][41][42][43][44][45][46], hot Brownian motion [47], and Brownian motion in shear flows [48]. Recent theoretical studies also found that the inertias of particles and surrounding fluids can significantly affect the Brownian motion in nonequilibrium systems [49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…The capability of such devices for separation of particles is rooted in the effect of entropic rectification, i.e., the rectification of motion caused by broken spatial symmetry caused by asymmetric variations of the accessible local volume [18][19][20]. The transport in channels with periodically varying cross-section exhibits peculiar transport phenomena [21][22][23][24][25][26] which can be treated by means of the so-termed Fick-Jacobs formalism and its generalizations [1,[27][28][29][30][31][32][33][34][35][36]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Для достаточно массивных частиц или наночастиц в газовой фазе не-обходим учет инерционных эффектов, при котором функция распределения приобретает дополнитель-ную зависимость от скорости и удовлетворяет го-раздо более сложному уравнению Клейна-Крамерса [6,7]. Инерционность броуновских моторов снимает ряд симметрийных ограничений, характерных для их безынерционных аналогов [8,9]. Наиболее впечат-ляющим примером является адиабатический режим флуктуаций знака потенциальной энергии.…”
Section: анализ литературных данных и постановка проблемыunclassified